Pendampingan dalam Produksi Konten Media Sosial Pelaku Usaha di Kecamatan Tamansari, Kabupaten Bogor - Joko Utomo Hadibroto; Aprilianti Pratiwi; Risma Kartika; Dian Nurkholiza Putri; Umi Hanifah (Jurnal Informasi Pengabdian Masyarakat, 2024)
Promotional activities are a crucial aspect of marketing products and services in business. With advancements in technology, marketing strategies have evolved towards digital approaches via social media, which offers various advantages for promotion, especially in the culinary industry. Business owners in Tamansari District, Bogor, face challenges due to insufficient digital promotion, resulting in low product visibility. This initiative aims to assist business owners in enhancing digital promotion through social media content production support. The method employed involves guidance from students and faculty members of the Faculty of Communication at Pancasila University. The outcomes, including logo updates, Instagram account creation, WhatsApp Business setup, and Google Maps registration, successfully increased the profile and visibility of the "Ok Snack" business. This initiative is expected to expand market reach and facilitate better consumer interaction.